THE VOLATILITY OF CRYPTOCURRENCY, DOLLAR AND COMPOSITE STOCK INDEX (JCI) FOR ESTIMATING VALUE AT RISK USING GARCH'S MODEL - Arif Hidayat Tumanggor (Jurnal Ekonomi, 2022)
This study was conducted to analyze the volatility of cryptocurrencies and predict VaR or value at Risk. Variables, Dollar Index, and Composite Stock Price Index (JCI) were used as independent variables. The cryptocurrency objects in this study are Bitcoin and Ethereum which have the largest market capitalization. The data in this study uses the period January 1, 2019 to December 31, 2021. This study uses GARCH analysis, Estimation of value at risk (VaR) using the GARCH model only works well on the Dollar. This is from the validity and more value it can be seen that the VaR estimate is lower and closer to the actual loss compared to Bitcoin and Ethereum. This situation has that Bitcoin and Ethereum are unstable and high risk compared to the Dollar.